Lean production as promoter of thinkers to achieve companies agility - Alves, Anabela Carvalho (2012)
Purpose Explore the Lean Production paradigm as promoter of workers’ creativity and thinking potential. Recognize this human potential as a fundamental asset for companies’ growth and success, being a major factor to face the disturbing and unpredictable needs of current markets, providing companies with the necessary agility. The authors believe these thinkers are the base for an Agile Company and Learning Organization. Design/methodology/approach The objectives were achieved through a deep literature review, starting with the Toyota Production System (TPS) origins. Some industrial Lean case studies were also explored to show that the adoption of a Lean culture promotes a pro-active attitude and behavior that are so important for companies nowadays. Findings This paper explores the association between Lean Production and the promotion of thinkers. For a long period and, even nowadays, it is common to consider the worker as just another production factor that the companies explore to obtain the maximum utilization. This was a result from the distorted knowledge of the Taylor principles and the Ford assembly line model, seeing the worker as a gear in the “big machine”. Lean Production was seen, for many years and by many authors, as an extension of this Taylorist/Fordist model but this paper highlights Lean Production as a work organization model where the worker assumes a position of thinker, continuously looking for improvement and continuously looking for wastes. By reducing wastes, the company will be prepared to accommodate changes and will attain agility. Research limitations/implications This paper is mainly based on literature review and on some industrial case studies of Lean implementations (recent or just a few years ago), being necessary a deep research on the cause-effect relation between Lean Production adoption and promotion of thinkers. Practical implications Helping the companies to recognize the importance of workers as thinkers will have relevant impacts through the reduction of waste and costs, improving quality and increase of productivity and revenue. Also, for the workers, this recognition means respect, self-esteem and confidence, and, essentially, more satisfaction with work. Social implications With Lean Production and agility, better products will quickly reach the society, contributing thus to clients’ satisfaction. Also, Lean companies’ CEO and workers looking for wastes will lead to a reduction of energy consumption, raw materials needs and gas emissions (reducing pollution of air, land and water), producing only what is needed. Being satisfied with their work they will be happier contributing to the raise of the country happiness. Originality/value The authors are not aware of a similar research. The paper is meant for those who are interested in improving their companies’ operations and workers’ relationships.